A third class of avian sarcoma viruses, defined by related transformation-specific proteins of Yamaguchi 73 and Esh sarcoma viruses. - Ghysdael, J (1981)
The gag-linked transformation-specific protein (polyprotein) p80 of Esh avian sarcoma virus (ESV) has been compared by tryptic peptide mapping with the homologous protein p90 of Yamaguchi 73 avian sarcoma virus (Y73). p80 of ESV and p90 of Y73 were found to share all four of their major nonstructural, transformation-specific, methionine-containing peptides and to have at least seven cysteine-containing transformation-specific peptides in common. Two nonstructural cysteine-containing peptides unique for ESV p80 and three specific for Y73 p90 were also identified. None of these peptides were found in the transforming gene product pp60src of Rous sarcoma virus (RSV) or in the transformation-specific polyproteins p105 of avian sarcoma virus PRCII (PRCII) or p140 of Fujinami sarcoma virus (FSV). ESV p80 and Y73 p90 are phosphorylated, and their tryptic phosphopeptides appear to be identical. In each polyprotein two major phosphopeptides were demonstrated, one containing phosphoserine, the other phosphotyrosine. The latter serves as phosphoacceptor for the protein kinase activities (ATP:protein phosphotransferase, EC 2.7.1.37) associated with p80 and p90. These protein kinase activities were found to be functionally indistinguishable but could be easily distinguished from the activities associated with PRCII p105 and FSV p140 on the basis of their cation requirement and target site specificity. On that basis also, p80/p90-associated protein kinases were found to be more similar to the enzymatic activity of pp60src than to those associated with the PRCII and FSV transformation-specific polyproteins. These results document a close genetic relationship between the two independently isolated sarcoma viruses Y73 and ESV. On the basis of the relatedness of transformation-specific proteins, ESV and Y73 constitute class III of avian sarcoma viruses, with class I containing the various strains of RSV and class II encompassing FSV and PRCII.